Efficient singlet oxygen generation from sugar pendant C60 derivatives for photodynamic therapy. Issue 93 (30th September 2015) - Yano, Shigenobu; Naemura, Masami; Toshimitsu, Akio; Akiyama, Motofusa; Ikeda, Atsushi; Kikuchi, Jun-ichi; Shen, Xiande; Duan, Qian; Narumi, Atsushi; Inoue, Masahiro; Ohkubo, Kei; Fukuzumi, Shunichi
Abstract : Glc-pendant C60 compounds exhibited high photocytotoxicity against HeLa cells due to the more efficient singlet oxygen generation as compared with that of Glc-pendant azafulleroids. Abstract : The amidation reaction between C60 with an activated ester group (1) and acetylated Glc (AcGlc) with an amino group (2) was performed to yield the target AcGlc-pendant C60 compound (3). The water soluble deacetylated compound, Glc-pendant C60 compound (4), exhibited high photocytotoxicity against HeLa cells due to the more efficient singlet oxygen generation as compared with that of Glc-pendant azafulleroids.